PENGEMBANGAN DIGITAL MARKETING PADA UMKM KAMPUNG SEMANGGI - Dwi Setyo Wibisono; Rachmadian Dwi Anggara; M. Harist Murdani; Alven Safik Ritonga (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Semanggi Village has several SMEs related to clover such as clover pecel, clover cake, clover clover and other small businesses. Partners in this service program are MSME entrepreneurs in the Semanggi Village area. The problems experienced by MSME entrepreneurs there include: (1) the lack of ability of target partners to marketing media, (2) public knowledge of the types of processed clover is still limited. This service program aims to develop the Semanggi Village website as a forum for various information related to Semanggi Village and as a digital media for marketing MSME products in Semanggi Village. The method used is a qualitative approach that focuses on the development of soft skills and critical thinking skills produced through assistance in using the website. Website development is expected to improve and maximize the marketing of typical products from Semanggi Village and hone critical thinking for target partners in Semanggi Hamlet, RW.03, Sememi Village. The results of this service program include: (1) the creation of the Semanggi Village website as a forum for information and also online marketing; (2) RW03 youth groups are able to understand and master how to manage and develop websites that have been created.